A Novel Kartogenin-Releasing Polymer Scaffold Promotes Wounded Rat Achilles Tendon Enthesis Healing. Issue 3 (14th September 2018) - Zhang, Jianying; Nie, Daibang; Zhao, Guangyi; Tan, Susheng; Hogan, MaCalus; Wang, James
Category: Hindfoot Introduction/Purpose: Entheses have a special fibrocartilage transition zone where tendons and ligaments attach to bone. Enthesis injury is very common, and the reattachment of tendon to bone is a great challenge because healing takes place between a soft tissue (tendon) and a hard tissue (bone). We have now developed a kartogene (KGN)-containing polymer scaffold (KGN-P) that can precisely deliver KGN to damaged enthesis area. The effects of the KGN-containing polymer on the healing of wounded TBJ were investigated in vitro and in vivo. Methods: The proliferation and chondrogenesis of rat Achilles tendon stem cells (TSCs) grown in four conditions were measured: normal medium (Control); normal medium with 100 nM KGN (KGN); lysine diisocyanate (LDI)-glycerol scaffold with normal medium (LDI-P); LDI-glycerol-KGN scaffold with normal medium (KGN-P).A wound (1 mm) was created on each hind leg Achilles enthesis of all 8 rats (3 months old). The wounds were then treated either with 10 ul saline (Wound); or 10 ul of 10 uM KGN (KGN); or LDI polymer scaffold (LDI-P); or KGN-containing polymer scaffold (KGN-P). The rats were sacrificed on day 15 and 30 post-surgery, and their Achilles entheses were collected for gross inspection and histochemical analysis. Results: KGN-containing polymers have sponge-like structures (Fig. 1A-D), and release KGN in a time- and temperature-dependent manner (Fig. 1E). KGN-P scaffold induced chondrogenesis of TSCs (Fig. 2D, 2H) without changing cell proliferation (Fig. 2I), and enhanced fibrocartilage-like tissue formation (Fig. 3E). KGN (Fig. 3C) and LDI-P (Fig. 3D) treated groups exhibited unhealed wound areas as in saline group (Fig. 3B). Finally, KGN-P and KGN treated rat TSCs underwent chondrogenesis by upregulating collagen II, aggrecan, and SOX-9 expression (Fig. 3F). Conclusion: Our results showed that KGN-containing polymer scaffold enhanced wounded enthesis healing by inducing TSC chondrogenesis and promoting the formation of the fibrocartilage in the wound site. The KGN-P may be used for regeneration of wounded entheses in clinical settings. Future research will focus on optimizing KGN concentration and releasing rate in the polymer scaffold during enthesis healing.